2019
DOI: 10.1590/0103-6440201902241
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Selective Versus Non-Selective COX-2 Inhibition on Experimental Periodontitis

Abstract: In the present study we compared the effects of the selective COX-2 inhibitor etoricoxib with those of the classical non-selective NSAID diclofenac on the inflammatory process and alveolar bone loss in an experimental model of periodontitis in rats. Ninety male Holtzman rats (250 g) were randomly sorted into four experimental groups: Sham+CMC and Ligature+CMC (control) groups which received 0.5% carboxymethylcellulose sodium (CMC) solution; Ligature+Diclofenac and Ligature+Etoricoxib groups which received Pota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 23 publications
1
6
1
1
Order By: Relevance
“…COX-2 acts as a mediator in the inflammatory pathways and strongly activates the inflammatory response by releasing pro-inflammatory cytokines like TNF-α and IL-1β [ 50 ]. It has been demonstrated that COX inhibitors could significantly reduce alveolar bone loss in periodontitis rats [ 51 , 52 ]. RANKL, a polypeptide of amino acids, binds to RANK on the cellular membranes of osteoclast precursors.…”
Section: Discussionmentioning
confidence: 99%
“…COX-2 acts as a mediator in the inflammatory pathways and strongly activates the inflammatory response by releasing pro-inflammatory cytokines like TNF-α and IL-1β [ 50 ]. It has been demonstrated that COX inhibitors could significantly reduce alveolar bone loss in periodontitis rats [ 51 , 52 ]. RANKL, a polypeptide of amino acids, binds to RANK on the cellular membranes of osteoclast precursors.…”
Section: Discussionmentioning
confidence: 99%
“…The crystal structure of 5c crystallized in the monoclinic space group P 2 1 /n with eight molecules in the unit cell. The lattice parameters were a = 12.0497(6)Å, b = 17.8324(10)Å, c = 19.6052(11)Å, α = 90.000 • , β = 100.372(1) • , γ = 90.000 • , and V = 4143.8(4)Å 3 . The asymmetric unit of 5c crystal structure showed two molecules which preferred the intramolecular C-H•••O interactions shown as a dotted line and 50% thermal ellipsoidal probability of non-hydrogen atoms (Table 3 and Figure 3).…”
Section: Crystallographymentioning
confidence: 99%
“…NSAIDs exhibit their anti-inflammatory activity via inhibition of cyclooxygenase (COX), an enzyme involved in the biosynthesis of prostaglandin G2 (PGG2). By inhibiting the formation of PGG2, the pathway, which would ultimately lead to the inflammatory response, is blocked [2,3]. The COX enzyme has two important isoforms, namely, COX-1 and COX-2.…”
Section: Introductionmentioning
confidence: 99%
“…Funções fisiológicas importantes são atribuídas à COX-1 através da síntese de prostanóides, como a manutenção da homeostase, proteção da mucosa gástrica e agregação plaquetária, que acabam por serem inibidas devido ao uso de AINEs (MORO et al, 2019). Reações comuns ao uso indiscriminado de AINEs incluem hipersensibilidade, dependência física e psíquica, encobrimento dos sintomas e agravamento de doenças de base (OLIVEIRA; PELÓGIA, 2011).…”
Section: Problemas Gerados Pelo Uso De Anti-inflamatórios: Alteraçõesunclassified